Origin, Migration, and Accumulation of Crude Oils in the Chaoyang Step-Fault Zone, Fushan Depression, Beibuwan Basin: Insight from Geochemical Evidence and Basin Modeling - Yang Shi; Hao Guo; Xiaohan Li; Huiqi Li; Meijun Li; Xin Wang; Surui Dong; Xi He (Energies)
The Fushan Depression is a hydrocarbon-rich depression in the Beibuwan Basin, South China Sea. In this study, 14 source rocks and 19 crude oils from the Chaoyang Step-Fault Zone and Southern Slope Zone were geochemically analyzed to determine their origins. The hydrocarbon generation, migration, and accumulation processes were also determined using two-dimensional basin modeling. Crude oils from the low-step area show a close relationship with the source rocks of the first and second members of the Eocene Liushagang Formation (Els1 and Els2). The oils from the middle-step area and the Southern Slope Zone are derived from the local source rocks in those areas, in the third member of the Eocene Liushagang Formation (Els3). Hydrocarbons generated from the Els3 source rocks of the Southern Slope Zone migrated along sand bodies to the Els3 reservoir. The fault system of the Chaoyang Step-Fault Zone controls hydrocarbon migration and accumulation in the low-step and middle-step areas. The resource potential of the middle-step area is limited by its shallow burial depth. The low-step area is a more favorable exploration area due to its proximity to the source kitchen.